2022
DOI: 10.46223/hcmcoujs.econ.en.12.2.2143.2022
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and outcomes of export market orientation: A bibliometric review

Abstract: Export market orientation has always been a central issue in the study of international business and marketing. Therefore, it is essential to put effort into understanding the concept and its application in real-life business. Following in-depth studies and critical review papers in previous years, this research paper focuses on synthesizing and analyzing empirical studies in the period from 2015 to 2021, revolving around theoretical issues, context, the main features of the object, and the methodology. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The estimated black tiger farm price elasticity with respect to export price of this study is also similar to what found in other previous studies. Specifically, Nguyen [37] and Le et al [38] found that the elasticity of farm price with respect to export price of back tiger shrimp were 0.1 and 0.3, respectively. Study results showed that this price elasticity is increasing in recent years.…”
Section: Price Transmission In the Long Runmentioning
confidence: 99%
“…The estimated black tiger farm price elasticity with respect to export price of this study is also similar to what found in other previous studies. Specifically, Nguyen [37] and Le et al [38] found that the elasticity of farm price with respect to export price of back tiger shrimp were 0.1 and 0.3, respectively. Study results showed that this price elasticity is increasing in recent years.…”
Section: Price Transmission In the Long Runmentioning
confidence: 99%
“…If actors invest or upgrade processing and preservation technology, the seasonal problem of products will be solved. The product will be preserved longer, meet market requirements, and reach further markets (Boaventura, Abdalla, Araujo, & Arakelian, 2018;FAO, 2015;Gashaw, Habteyesus, & Nedjo, 2018; H. T. T. Nguyen & Mai, 2017; L. T. P. Nguyen, 2017;P. V. Nguyen & To, 2014;S.…”
Section: Solutions To Upgrade the Value Chainmentioning
confidence: 99%